1998
DOI: 10.1038/sj.bmt.1701422
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human granulocyte and granulocyte–macrophage colony-stimulating factor (G-CSF and GM-CSF) administered following cytotoxic chemotherapy have a similar ability to mobilize peripheral blood stem cells

Abstract: Summary:The availability of hematopoietic growth factors has greatly facilitated the mobilization and collection of peripheral blood stem cells (PBSC). It was the aim of this double-blind study to compare the PBSC-mobilizing efficacy of recombinant human G-CSF and GM-CSF when administered post-chemotherapy. Twenty-six patients with relapsed Hodgkin's disease were included in the study. Their median age was 31 years (range, 22-59) and 14 patients were males and 12 were females. Patients were pretreated with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 10 publications
(12 reference statements)
2
22
0
Order By: Relevance
“…The total number of progenitors collected, and median time to platelet and neutrophil engraftment, were similar for both groups. A number of chemotherapy-based mobilizing regimens has been reported in lymphoma patients, [32][33][34][35] however, only one is a randomized comparison to cyclophosphamide alone. 32 That trial compared ifosfamide 10 g/m 2 and GM-CSF to cyclophosphamide 4 g/m 2 and GM-CSF and reported similar CD34 + yields, but improved neutrophil engraftment and less toxicity with cyclophosphamide.…”
Section: C+e C (Matched Controls)mentioning
confidence: 99%
“…The total number of progenitors collected, and median time to platelet and neutrophil engraftment, were similar for both groups. A number of chemotherapy-based mobilizing regimens has been reported in lymphoma patients, [32][33][34][35] however, only one is a randomized comparison to cyclophosphamide alone. 32 That trial compared ifosfamide 10 g/m 2 and GM-CSF to cyclophosphamide 4 g/m 2 and GM-CSF and reported similar CD34 + yields, but improved neutrophil engraftment and less toxicity with cyclophosphamide.…”
Section: C+e C (Matched Controls)mentioning
confidence: 99%
“…However, one randomized trial compared filgrastim to molgramostim in 26 patients with Hodgkin's disease receiving MC. 16 Twenty-one patients completed PBSC collections and there were no differences in CD34 + cell yields or toxicities between the two groups. 16 Bregni et al, 18 in a non-randomized trial, compared filgrastim to molgramostim administered by continuous intravenous infusion in 49 patients with malignant lymphoma receiving cyclophosphamide 7 g/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Twenty-one patients completed PBSC collections and there were no differences in CD34 + cell yields or toxicities between the two groups. 16 Bregni et al, 18 in a non-randomized trial, compared filgrastim to molgramostim administered by continuous intravenous infusion in 49 patients with malignant lymphoma receiving cyclophosphamide 7 g/m 2 . 18 These investigators found more rapid recovery of neutrophils following filgrastim (P = 0.01), more rapid recovery of platelets following molgramostim (P = 0.01), and more CD34 + cells/kg/apheresis following molgramostim (the latter difference not being statistically significant, P = 0.132).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations